The role of the prosecutor’s office in observing the rights and freedoms of citizens of the Kyrgyz Republic (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
Human rights and freedoms, as well as their protection by state bodies is a fundamental principle for the development of any modern state. Consideration of the relevance of this article through the prism of the activities of the prosecutor’s office as a state body with a special status allows us to identify important areas and highlight the special role of the prosecutor’s office in the formation of the legal society of the Kyrgyz Republic. By studying the specifics of the activities and a wide range of issues that the prosecutor’s office deals with, the results of this article familiarise with its functions and exemplary direction, which in turn allows to prevent and prevent violations of the rights and freedoms of citizens of the Kyrgyz Republic.
Keywords: prosecutor’s office, human rights, supervision, order, execution, legality, government bodies, competence, exception